A dinâmica da sociocomunicação no ciberespaço: o impulso alquímico - Oliveira, Walter Clayton de [UNESP] (Universidade Estadual Paulista (Unesp), 2005)
The Cyberspace is a colossal tissue, a communication device that associates multiple and opposed characteristics. When developing in a spontaneous way, the Cyberspace begins then to guide for the communication. Don't lack countless communication communities today. In this sense, we objectified with this research, to analyze the dynamics of the social communication, transfer and flow of information in virtual communities, took as self-organized social systems, in the Cyberspace. Through incursions in the literature, we made a theoreticaldescriptive analysis of the social communication concept and we discussed in what measure could be applied to the interrelations that emerge among the individuals belonging to the virtual communities. We conclude that, the Cyberspace, thus defined, is configured as one locus of extreme complexity and difficult understanding. Its heterogeneous is well-known when the great existing environment number is perceived of sociability, in the interior of which if they establish most diverse and varied interaction forms, as much between Men, how much between Men and machines and, also, between machines. One is about a new type of social technique organization that facilitates the mobility in and of the knowledge, the exchanges to know, the collective construction of the direction, where the identity suffers an expansion from based self in the dilution the body, or either, what it is lost in body gains in rapidity and capacity to spread self in the space-time. It is attended, thus, to an acceleration of the social metabolism.

O Ciberespaço é uma teia colossal, um dispositivo de comunicação que associa características múltiplas e opostas. Ao desenvolver-se de forma espontânea, o Ciberespaço começa então a orientar-se para a comunicação. Não faltam hoje inúmeras comunidades de comunicação. Neste sentido, objetivamos com esta pesquisa, analisar a dinâmica da sociocomunicação, transferência e fluxo de informações de comunidades virtuais tomadas como sistemas sociais auto-organizados, no Ciberespaço. Através de incursões na literatura, fizemos uma análise teórica-descritiva do conceito de sociocomunicação e discutimos em que medida ele pode ser aplicado diante das inter-relações que emergem entre os indivíduos pertencentes às comunidades virtuais. Concluímos que, o Ciberespaço, assim definido, configura-se como um locus de extrema complexidade e difícil compreensão. A sua heterogeneidade é notória quando se percebe o grande número de ambientes de sociabilidade existentes, no interior dos quais se estabelecem as mais diversas e variadas formas de interação, tanto entre Homens, quanto entre Homens e máquinas e, inclusive, entre máquinas. Trata-se de um novo tipo de organização sociotécnica que facilita a mobilidade no e do conhecimento, as trocas de saberes, a construção coletiva do sentido, em que a identidade sofre uma expansão do eu baseada na diluição da corporeidade, ou seja, o que se perde em corpo ganha-se em rapidez e capacidade de disseminar o eu no espaço-tempo. Assiste-se, assim, a uma aceleração do metabolismo social.
Keywords: Sociabilidade; Ciberespaço; Internet; Redes de computadores; Informática - Aspectos sociais; Sistemas auto-organizadores; Sociocomunicação; Auto-organização; Transferência de informação; Cyberspace; Self-organization; Transfer of information